PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PESONA SINAR WISATA DI JAKARTA TIMUR - Fadli Aditya Syahputra; Styo Budi Utomo (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of leadership style and work motivation on the performance of employees of PT Pesona Sinar Wisata East Jakarta. The sampling method used in this study was a saturated sample by taking the entire population as a sample. This type of research is quantitative up to 86 employees. This study uses quantitative analysis methods, namely the use of in-depth analysis of data in the form of numbers. Data processing and analysis techniques used descriptive analysis, data instrument testing, classical hypothesis testing, correlation and determination test, hypothesis testing. Leadership style and work motivation at PT Pesona Sinar Wisata East Jakarta have a positive and significant effect on employee performance at PT Pesona Sinar Wisata East Jakarta with the regression equation Y = 7.507 + 0.361 X1 + 0.431 X2. These results indicate that the simultaneous correlation coefficient is 0.554 and the coefficient of determination which is simultaneously 0.643. With this leadership style on employee performance with a value of tcount> ttable which is 6.096> 1.663 with a significant value of 0.000 <0.005. Then, work motivation on employee performance with a value of tcount> ttable which is 6.297> 1.663. while Fcount> Ftable is 29.207> 2.712 with a significant level of 0.000 <0.05. We can therefore conclude that leadership style and motivation at work have a significant influence on employee performance.